2013
DOI: 10.1590/s0034-737x2013000400002
|View full text |Cite
|
Sign up to set email alerts
|

Atividade proteolítica de bactérias psicrotróficas em leites estocados em diferentes temperaturas

Abstract: Proteolytic activity of psychrotrophic bacteria in milk stored at different temperaturesThe widespread use of cooling technology as a tool for maintaining the microbiological and organoleptic characteristics of milk, Without effective hygienic practices throughout the milk production, caused the psychrotrophic micro-organisms to become major deteriorative bacteria in the dairy industry. The present study aimed to assess how the proteolytic psychrotrophic metabolism responds to different milk storage temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The association between the increase in milk temperature and the increase in SPC is possibly related to milk with higher temperature favors the multiplication of microorganisms, mainly mesophilic. Izidoro, Pereira, Soares, Spina and Pinto (2013) observed that the SPC increased as the temperature and storage time increased in milk stored at different temperatures. The factors formed shown that basic actions such as the proper planning of the collection and transport routes for milk, with shorter and faster routes, good practices in primary production, and technical guidance for the dairy farmers and transporters are essential for good milk quality.…”
Section: Resultsmentioning
confidence: 93%
“…The association between the increase in milk temperature and the increase in SPC is possibly related to milk with higher temperature favors the multiplication of microorganisms, mainly mesophilic. Izidoro, Pereira, Soares, Spina and Pinto (2013) observed that the SPC increased as the temperature and storage time increased in milk stored at different temperatures. The factors formed shown that basic actions such as the proper planning of the collection and transport routes for milk, with shorter and faster routes, good practices in primary production, and technical guidance for the dairy farmers and transporters are essential for good milk quality.…”
Section: Resultsmentioning
confidence: 93%
“…The sample storage time did not affect the PMC (p = 0.9012) in milk samples preserved with azidiol ® , while milk samples not added with this preservative showed a linear increase in PMC with progressing time (hours) (p < 0.0001). Izidoro, Pereira, Soares, Spina and Pinto (2013) evaluated the PMC of milk samples at different storage times (12, 24, and 48 hours) and temperatures (4, 8, and 12°C) and concluded that, regardless of the storage temperature, PMC always increased with increasing storage time. Reche et al (2015) observed higher PMC in bulk milk tanks of the model of 'four milkings', and related such results to the higher storage temperature compared to the bulk milk tanks of the model of 'two milkings' since the latter have a greater capacity for faster cooling of milk.…”
Section: Resultsmentioning
confidence: 99%
“…According to this regulation, milk must be kept refrigerated at a temperature of 4°C and stored on the rural property for a maximum of 48 hours. This refrigeration practice aims to control the proliferation of mesophilic aerobic bacteria, whose count reflects the hygiene conditions up to the milking moment, serving as an indicator of the effectiveness of the milk refrigeration system (Izidoro et al, 2013). This regulation plays a crucial role in ensuring the quality and safety of milk produced in the country.…”
Section: Introductionmentioning
confidence: 99%